Digitale Versorgungsformen zur Personalisierung der stationsäquivalenten Behandlung - Rauschenberg, Christian; Hirjak, Dusan; Ganslandt, Thomas; Schulte-Strathaus, Julia C. C.; Schick, Anita; Meyer-Lindenberg, Andreas; Reininghaus, Ulrich (Der Nervenarzt, 2021)
Background: Ward-equivalent treatment (StäB), a form of crisis resolution and home treatment in Germany, has been introduced in 2018 as a new model of mental health service delivery for people with an indication for inpatient care. The rapid progress in the field of information and communication technology offers entirely new opportunities for innovative digital mental health care, such as telemedicine, eHealth, or mHealth interventions. Objective: This review aims to provide a comprehensive overview of novel digital forms of service delivery that may contribute to a personalized delivery of StäB and improving clinical and social outcomes as well as reducing direct and indirect costs. Method: This work is based on a narrative review. Results: Four primary digital forms of service delivery have been identified that can be used for personalized delivery of StäB: (1) communication, continuity of care, and flexibility through online chat and video call; (2) monitoring of symptoms and behavior in real-time through ecological momentary assessment (EMA); (3) use of multimodal EMA data to generate and offer personalized feedback on subjective experience and behavioral patterns as well as (4) adaptive ecological momentary interventions (EMI) tailored to the person, moment, and context in daily life. Conclusion: New digital forms of service delivery have considerable potential to increase the effectiveness and cost-effectiveness of crisis resolution, home treatment, and assertive outreach. An important next step is to model and initially evaluate these novel digital forms of service delivery in the context of StäB and carefully investigate their quality from the user perspective, safety, feasibility, initial process and outcome quality as well as barriers and facilitators of implementation.
CRIS-Team Scopus Importer:2021-11-16
Keywords: Digital intervention; Ecological momentary intervention; eHealth; Mobile health; Telemedicine